Moderation of assessments in a School of Nursing and Midwifery: Enhancing student assessment experiences - Andrew, L.; Ewen, B.; Scott, Rowena (FYHE, 2014)
This paper details a quality improvement initiative undertaken in 2013 within a School of Nursing and Midwifery, in Western Australia. The objective of the initiative was to support and enhance commencing student assessment experiences through the development of evidence based, standardised assessment of moderation process.